Efficacy of first-line CDK 4-6 inhibitors in premenopausal patients with metastatic breast cancer and the effect of dose reduction due to treatment-related neutropenia on efficacy: a Turkish Oncology Group (TOG) study - Yildirim, Hasan Cagri; Kapar, Caner; Koksal, Baris; Seyyar, Mustafa; Sanci, Pervin Can; Guliyev, Murad; Aksoy, Sercan (Taylor & Francis Ltd, 2025)
The only phase 3 study on the effectiveness of CDK 4-6 inhibitors in first-line treatment in premenopausal patients with hormone receptor (HR) positive, HER2 negative metastatic breast cancer is the MONALEESA-7 study, and data on the effectiveness of palbociclib is limited. Data are also limited regarding the effectiveness of CDK 4-6 inhibitors in patients whose dose was reduced due to neutropenia, the most common side effect of CDK 4-6 inhibitors. In our study, we aimed to evaluate the effectiveness of palbociclib and ribociclib in first-line treatment in patients with premenopausal metastatic breast cancer and the effect of dose reduction due to neutropenia on progression-free survival. Our study is a multicenter, retrospective study, and factors affecting progression-free survival (PFS) were examined in patients diagnosed with metastatic premenopausal breast cancer from 29 different centers and receiving combination therapy containing palbociclib or ribociclib in the metastatic stage. 319 patients were included in the study. The mPFS for patients treated with palbociclib was 26.83 months, and for those receiving ribociclib, the mPFS was 29.86 months (p = 0.924). mPFS was 32.00 months in patients who received a reduced dose, and mPFS was 25.96 months in patients who could take the initial dose, and there was no statistical difference (p = 0.238). Liver metastasis, using a fulvestrant together with a CDK 4-6 inhibitor, ECOG PS 1 was found to be a negative prognostic factor. No new adverse events were observed. In our study, we found PFS over 27 months in patients diagnosed with premenopausal breast cancer with CDK 4-6 inhibitors used in first-line treatment, similar to post-menopausal patients. We did not detect any difference between the effectiveness of the two CDK 4-6 inhibitors, and we showed that there was no decrease in the effectiveness of the CDK 4-6 inhibitor in patients whose dose was reduced due to neutropenia.
Keywords: Premenopausal breast cancer; low-dose treatment